The disconnect about displacement: Parental perspectives on IDP access to education in Iraq in the COVID-19 Era - Mariam Hassoun (Educational Futures)
Over six million Iraqis were displaced during the war with Daesh, and although many have returned to their communities, there are approximately 1.3 million internally displaced persons (IDPs) scattered across the country. Many IDP children in Iraq, whether in camps or in host communities, face challenges related to poor infrastructure, documentation, economic insecurity, trauma, and health shocks that make it difficult to access schooling. These shocks were compounded by the COVID-19 pandemic which led to nine months of nationwide school closures supported by some temporary use of online educational alternatives. However, distance learning is not accessible to the 50% of Iraq’s population without in-home internet access (ACAPS, 2020). This qualitative study explores how IDP parents of the Iraq-Daesh War describe the impacts of COVID-19 on their ward’s educational access, particularly ramifications of the digital divide and repeated iterations of extended educational interruptions. The COVID-19 pandemic has essentially halted all progress towards educational access in the IDP community in Iraq due to lack of facilities appropriate for social distancing and inadequate access to internet and technology necessary for distance learning. The findings call into question the predominant recommendation of e-learning in fragile context and raises concerns about the worsening of educational inequality under a reinforced digital divide. The research also indicates future opportunity to identify potential emergency education interventions through study of grassroots initiatives established by IDPs.